Flow Field and Particle Flow of Two-Stage Deep-Sea Lifting Pump Based on DEM-CFD - Yuanwen, Li; Zhiming, Guo; Liu, Shaojun; Xiaozhou, Hu (Frontiers in Energy Research, 2022)
Through discrete element method-computational fluid dynamics, the internal flow field and particle motion law of a two-stage deep-sea lifting pump at different rotational speeds were analyzed in this work. In addition, the physical phenomena, such as flow field velocity, secondary flow, and particle flow, were studied. The relationship between the rotational speed of the lifting pump and solid–liquid two-phase flow was investigated. An experiment on the hydraulic performance of the lift pump showed that the resulting lift and efficiency were consistent with the numerical simulation data. When the rotational speed was 1,450 rpm, the particles can obtain a higher kinetic energy from the flow field, the flow was more stable, and particle deposition was reduced.